Interactions between high power fiber laser and rock in shaley formation during drilling and production operation - Bazargan, M. (European Association of Geoscientists and Engineers, EAGE, 2014)
This paper is presenting the data on interactions between Fiber laser and shale. With this obvious goal that is dependent on improving the efficiency of laser power. The idea of selecting shale sample was because of variety of this rock type in Iranian oil and gas formations. In the experiment, a long pulsed laser beam was arranged to drill and propagate surfaces, in the opposite direction to the earth gravity, and it was used to drill hole from the top to the bottom of cylindrical Shale rock. The heat that been induced from the Fiber laser is absorbed in the direct surfaces in front and cause heat flux generation inside of rock texture. The specific heat transfer inside of shale sample can cause effects on many physical parameters such as porosity, permeability and resistivity. In the point of heat source, the temperature of the area can increase up to 500 - 1700o C, this temperature can show the influence of itself in fluid and solid materials that combine together in the porous medium. In this work we focused on effects of fiber laser heat generation on solid and fluid that been included in saturated shale. Copyright Â© 2014 by the European Association of Geoscientists & Engineers. All rights reserved.